Public-private partnerships and the reduction of undernutrition in developing countries - Hoddinott, John F.; Gillespie, Stuart; Yosef, Sivan (International Food Policy Research Institute, 2015)
This paper brings structure to the discussion of private-sector engagement in nutrition by clarifying different models of engagement, reviews the evidence base on public-private partnerships (PPPs) for the reduction of undernutrition, and outlines some potential ways forward. We find that there are few independent, rigorous assessments of the impact of commercial-sector engagement in nutrition. Considerable caution is thus warranted when assessing PPPs in nutrition. Looking forward, future progress requires that the private sector recognize that past and current actions by some firms have created an environment of mistrust. It requires that the public sector accept that sustainable PPPs are those which permit private firms to generate profits. There is significant scope for the private sector to drive innovations that could reduce undernutrition, and, more speculatively, there may be scope for the private sector to act as a financier. Underpinning all these efforts must lie open discussions of the objectives, roles, and expectations of all parties along with potential conflicts of interest; an open space or platform where issues and challenges can be discussed and addressed; incentives for the private sector to take on pro-nutrition roles; strong, transparent, and well-enforced monitoring processes; and serious, independent evaluations of these activities.